Transcriptome Profiling Using Single-Molecule Direct RNA Sequencing Approach for In-depth Understanding of Genes in Secondary Metabolism Pathways of Camellia sinensis - Xu, Qingshan; Zhu, Junyan; Zhao, Shiqi; Hou, Yan; Li, Fangdong; Tai, Yuling; Wan, Xiaochun; Wei, ChaoLing (Frontiers in Plant Science, 2017)
Characteristic secondary metabolites, including flavonoids, theanine and caffeine, are important components of Camellia sinensis, and their biosynthesis has attracted widespread interest. Previous studies on the biosynthesis of these major secondary metabolites using next-generation sequencing technologies limited the accurately prediction of full-length splice isoforms. Herein, we applied single-molecule sequencing to pooled tea plant tissues, to provide a more complete transcriptome of Camellia sinensis. Moreover, we identified 94 full-length transcripts and four alternative splicing events for enzyme-coding genes involved in the biosynthesis of flavonoids, theanine and caffeine. According to the comparison between long-read isoforms and assemble transcripts, we improved the quality and accuracy of genes sequenced by short-read next-generation sequencing technology. The resulting full-length transcripts, together with the improved assembled transcripts and identified alternative splicing events, enhance our understanding of genes involved in the biosynthesis of characteristic secondary metabolites in Camellia sinensis.